Development Of Logic And Algorithm E-Training Material With Block Programming - Prayitno Prayitno; Liliek Triyono (Politeknik Negeri Semarang, 2017)
Integrating logical and analytical thinking activities to support 21st century learning ability, into a learning activity at elementary and junior high school level becomes a challenge. One of them is less interesting learning media. One of the technologies that can be used to support exciting learning is block programming Alice and Scratch. This article aims to develop online training materials Logic and Algorithm utilize block programming scratch for level five elementary school and block programming Alice for level eight junior high school as eLearning content. The development of this research is carried out by Analysis-Design-Development-Implementation-Evaluation (ADDIE) development model. Initial products were reviewed and advised by 2 primary school teachers, 2 junior high school teachers. Product quality assessment is done based on content feasibility aspect, feasibility of presentation, language feasibility using Likert scale. The results data are then analyzed using the ideal scoring criteria to determine product quality. The results of the overall training content quality assessment show an average grade of 89.8 with good.